Sitharaman’s 16-point plan for agri may not work if she does not do this - Saroj, Sunil; Roy, Devesh; Pradhan, Mamata (Indian Express Group, 2020)
Unless the government builds in right incentives for its agriculture action plan, things will not work. As has been the case with e-NAM and banana trains.